2015
DOI: 10.1097/nmd.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Social Functioning and Age Across Affective and Nonaffective Psychoses

Abstract: Both non-affective and affective psychoses are associated with deficits in social functioning across the course of the illness. However, it is not clear how social functioning varies among diagnostic groups as a function of age. The current study examined the relationship between social functioning and age in schizophrenia (SZ), schizoaffective disorder (SZA), and psychotic bipolar disorder (PBD). We found that individuals with PBD had the highest functioning while individuals with SZ had the poorest. The func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
(59 reference statements)
2
9
1
1
Order By: Relevance
“…In this sense, age may modify individual patients’ perceptions of their capacity/ability to perform daily activities, being the older patients more inclined to perceive themselves as more impaired and to report more difficulties in their day to day functioning. There is also one study pointing out that the impact of increasing age on a poorer functioning is regardless of the diagnosis (schizophrenia, bipolar disorder, or schizoaffective disorder) .…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, age may modify individual patients’ perceptions of their capacity/ability to perform daily activities, being the older patients more inclined to perceive themselves as more impaired and to report more difficulties in their day to day functioning. There is also one study pointing out that the impact of increasing age on a poorer functioning is regardless of the diagnosis (schizophrenia, bipolar disorder, or schizoaffective disorder) .…”
Section: Discussionmentioning
confidence: 99%
“…Negative symptoms can be conceptualised as the absence or reduction in normal affective, behavioural and social functioning, and are one of the biggest predictors of quality of life for people with schizophrenia and social recovery . Whilst psychotic symptoms generally recede in older age, negative symptoms persist and older people are more likely to report problems with social functioning compared to both younger people with the condition and same age‐peers without the diagnosis, including those with other types of mental health problems …”
Section: Introductionmentioning
confidence: 99%
“…symptoms persist 6 and older people are more likely to report problems with social functioning compared to both younger people with the condition and same age-peers without the diagnosis, including those with other types of mental health problems. 7 Research demonstrates the effectiveness of psychosocial interventions for improving social functioning in schizophrenia. 8,9 For example, one meta-analysis reported that cognitive behaviour therapy had a mean weighted effect size of 0.38 on functioning.…”
mentioning
confidence: 99%
“…Among patients affected by psychotic disorders, schizophrenia patients display the highest deficit in social functioning. 3 , 4 Social functioning has been recognized as an important contributor to overall quality of life and a determinant of treatment success. 4 Cognitive impairments impact functioning skills in schizophrenia patients and it is known that positive and negative symptoms add to the influence of cognitive impairments for prediction of real-world outcomes.…”
Section: Introductionmentioning
confidence: 99%